The recommended lifetime immunization schedule from the board of vaccination calendar for life in Italy: A continuing example of impact on public health policies. Issue 8 (22nd February 2021) - Bonanni, P.; Villani, A.; Scotti, S.; Biasci, P.; Russo, R.; Maio, T.; Vitali Rosati, G.; Moscadelli, A.; Conforti, G.; Azzari, C.; Ferro, A.; Francia, F.; et al.
Abstract: The Vaccination Calendar for Life is an alliance of scientific and professional societies of public health physicians, paediatricians and general practitioners in Italy which provides a periodical update on the ideal, scientifically driven vaccination calendar throughout lifetime. Since 2012, the Lifetime Immunization Schedule has represented a benchmark for Regional and National Authorities to set up the updated list of vaccines provided actively and free of charge to infants, children, adolescents, adults and the elderly by inclusion in the Triennial National Vaccination Plan (TNVP), and in the Essential Levels of Care (LEA). The impact of the different editions of the Lifetime Immunization Schedule on the TNVP was deep, representing the inspiring source for the present vaccination policy. The 2019 edition called for more attention to pregnant women immunization; risk groups vaccination; uniform high coverage with the MMRV vaccine; extension of Meningococcal B vaccination also at adolescent age; use of quadrivalent conjugate meningococcal vaccine also at 1 year of life; progressive decrease of the age of free-of-charge offer of influenza to ≥ 60 and then to ≥ 50 year-old population; implementation of flu immunization ages 6 months-6 years; HPV vaccination also offered to 25-year old women at the time of the first screening (gender neutral immunization already offered); sequential PCV13-PPV23 pneumococcal vaccination in 65 year-old subjects; increased coverage with rotavirus vaccine in infants and zoster vaccine in the elderly.